2019
DOI: 10.26603/ijspt20190415
|View full text |Cite
|
Sign up to set email alerts
|

COMPARISON of LOWER QUARTER Y-BALANCE TEST SCORES for FEMALE COLLEGIATE VOLLEYBALL PLAYERS BASED on COMPETITION LEVEL, POSITION, and STARTER STATUS

Abstract: Background: The Lower Quarter Y-Balance Test (YBT-LQ) is used by sports medicine professionals to measure an athlete's dynamic balance. The YBT-LQ is used by clinicians to track recovery during clinical rehabilitation, assess an athlete's readiness to return to sport after injury, and to identify athletes potentially at-risk for a time-loss injury. Normative data for the YBT-LQ are lacking for female collegiate volleyball (VB) players. The purpose of this study was to examine preseason YBT-LQ scores and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…In terms of static balance abilities and postural priority, Jadczak et al [16] reported signi cant differences between playing positions, with mid elders achieving better results than the other playing positions. These ndings go in line with Brumitt et al [17] who detected signi cantly greater posterolateral and composite reach measures bilaterally in the Lower Quarter Y Balance Test (YBT-LQ) in liberos/defensive specialists/setters. In baseball, a sport comparable to handball in terms of upper extremity importance, Ryu et al [18] were able to detect signi cant differences between the pitchers and in elders in mean right posteromedial normalized reach distances and the composite score executing the YBT-LQ.…”
Section: Discussionsupporting
confidence: 89%
“…In terms of static balance abilities and postural priority, Jadczak et al [16] reported signi cant differences between playing positions, with mid elders achieving better results than the other playing positions. These ndings go in line with Brumitt et al [17] who detected signi cantly greater posterolateral and composite reach measures bilaterally in the Lower Quarter Y Balance Test (YBT-LQ) in liberos/defensive specialists/setters. In baseball, a sport comparable to handball in terms of upper extremity importance, Ryu et al [18] were able to detect signi cant differences between the pitchers and in elders in mean right posteromedial normalized reach distances and the composite score executing the YBT-LQ.…”
Section: Discussionsupporting
confidence: 89%
“…The dynamic balance scores have been used to screen deficits in neuromuscular control due to pathologies [ 41 , 42 , 43 , 44 ], injury prediction [ 45 , 46 , 47 ], the effect of a certain treatment [ 44 , 48 , 49 , 50 ], or rehabilitation/physical activity program [ 42 , 51 , 52 , 53 , 54 ] in patients with various diseases and return to sport readiness [ 55 , 56 ]. Furthermore, the performance delivered in these tests has also been positively related to physical fitness [ 57 , 58 ] and sports performance [ 22 , 23 , 59 ]. The present results are in tandem with the literature, as higher scores in the UQ-YBT (better upper quarter dynamic balance) were correlated to faster swimming speeds (better performance).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic balance and, notably, the upper quarter Y-balance Test (UQ-YBT) have been selected to monitor swimmers less than a handful of times as far as our understanding goes. Studies explored the differences in balance scores between athletes of different sports [ 20 ], competitive levels [ 21 , 22 , 23 ], and under different types of training regimes [ 24 ]. One study selected the UQ-YBT as a benchmark standard to validate another balance test in adolescent swimmers [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance and contrary to our findings, Patel and Choudhary 19 were able to detect significant differences in balance performance as assessed through the long nose test between the playing positions of handball players in favor of right wingers when compared with center players ( p =0.001), goalkeepers ( p <0.001), back left ( p =0.003), and back right ( p <0.001) as well as pivots ( p <0.001). Further, Brumitt et al 20 reported significant differences in the Lower Quarter Y-Balance Test (YBT-LQ) between volleyball players with different playing positions, with liberos, defensive specialists, and steers taken together displaying significantly better results (posterolateral reach direction: 106.1±10.7% leg length, p =0.001; CS: 106.9±12.8% leg length, p <0.001) than the outside hitters, middle blockers, and opposite right side hitters (posterolateral reach direction: 99.8±10.6% leg length; CS: 94.8±10.8% leg length) when the right lower extremity was tested. Also for the left lower extremity, significantly (posterolateral reach direction: p =0.002; CS: p <0.001) better results were reported for the liberos, defensive specialists, and steers taken together (posterolateral reach direction: 105.8±9.1% leg length; CS: 1070.0±11.4% leg length) than for the outside hitters, middle blockers, and opposite right hitters taken together (posterolateral reach direction: 100.1±10.8% leg length; CS: 95.6±10.4% leg length).…”
Section: Discussionmentioning
confidence: 98%